Neurologic, Gastric, and Opthalmologic Pathologies in a Murine Model of Mucolipidosis Type IV - Venugopal, Bhuvarahamurthy (American Society of Human Genetics, 2007)
Mucolipidosis type IV (MLIV) is an autosomal recessive lysosomal storage disorder caused by mutations in the MCOLN1 gene, which encodes the 65-kDa protein mucolipin-1. The most common clinical features of patients with MLIV include severe mental retardation, delayed motor milestones, ophthalmologic abnormalities, constitutive achlorhydria, and elevated plasma gastrin levels. Here, we describe the first murine model for MLIV, which accurately replicates the phenotype of patients with MLIV. The Mcoln1(−/−) mice present with numerous dense inclusion bodies in all cell types in brain and particularly in neurons, elevated plasma gastrin, vacuolization in parietal cells, and retinal degeneration. Neurobehavioral assessments, including analysis of gait and clasping, confirm the presence of a neurological defect. Gait deficits progress to complete hind-limb paralysis and death at age ∼8 mo. The Mcoln1(−/−) mice are born in Mendelian ratios, and both male and female Mcoln1(−/−) mice are fertile and can breed to produce progeny. The creation of the first murine model for human MLIV provides an excellent system for elucidating disease pathogenesis. In addition, this model provides an invaluable resource for testing treatment strategies and potential therapies aimed at preventing or ameliorating the abnormal lysosomal storage in this devastating neurological disorder.